One-dimensional Analysis of Impulse Turbine with Self-pitch-controlled Guide Vanes for Wave Power Conversion. (2000) - Inioue Inioue, M. M.; Kaneko Kaneko, K. K.; Setoguchi Setoguchi, T. T.
Abstract : A classical one-dimensional analysis in turbomachinery was presented to estimate aerodynamic characteristics of an impulse turbine with self-pitch-controlled guide vanes which is proposed by the authors for ocean wave power conversion. With some simplified assumptions, the efficiency vs/flow-rate coefficient curves were calculated and compared with the experimental results both in a unidirectional steady flow condition and a sinusoidally oscillating flow condition. The estimated results reveal a behavior of the actual characteristics curve of the turbine. Possibility of further improvement in efficiency was discussed from a viewpoint of specific speed and specific diameter.